HEPATIC EXINOCOCCOSIS-CLINICAL FEATURES AND TREATMENT APPROACHES OF PARASITIC DISEASE (World Bulletin of Public Health, 2025)
Hepatic exinococcosis is a parasitic disease called Echinococcus granulosus or Echinococcus multilocularis, which forms hydatidous cysts in the human body. This disease is usually chronic and causes the formation of cysts in the liver and other organs. Exinococcosis can be transmitted from animals to humans, and the lack of compliance with sanitary and hygienic rules leads to its widespread distribution
Keywords: Liver exinococcosis; parasitic diseases; exinococcal cyst